Seleksi In Vitro Embrio Somatik Kacang Tanah pada Medium dengan Polietilen Glikol untuk Simulasi Kondisi Cekaman Kekeringan - Enni Suwarsi Rahayu; Satriyas Ilyas; Sudarsono Sudarsono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
This study was aimed to evaluate the effectiveness of in vitro selection for identifying PEG insensitive somaclonal variant of peanut somatic embryos (SE). In one of the experiments,  evaluation on responses of four peanut cultivars against selective medium containing polyethylene glycol 6000 (PEG 6000) was conducted and sub-lethal concentration of PEG was determined. In the other experiment, in vitro selection on selective medium containing sub-lethal level of PEG was conducted to identify PEG insensitive SE of peanut. Secondary SE of peanut cv. Badak, Kelinci, Singa, and Zebra were cultured on liquid MS medium supplemented with 16 µM of picloram and 5%, 10%, 15%, or 20% of PEG 6000. Survival of explant, average number of proliferated SE/explant, and total number of proliferated SE after in vitro selection were recorded monthly, up to three months. Sub-lethal level of PEG was defined as one inhibiting more than 95% of the total number of proliferated SE. In vitro selection on medium supplemented with sub-lethal level of PEG 6000 was conducted on at least 4000-5000 SE of peanut cv. Kelinci and Singa. The PEG insensitive SE was identified after subsequent three months of in vitro selection. The results showed that supplementation of PEG 6000 on medium for induction of SE inhibited proliferation of peanut SE. Sub-lethal level was obtained at 15% concentration of PEG 6000. The frequencies of obtaining PEG insensitive SE of peanut cv. Kelinci was 8% to 10%  and for peanut cv. Singa was 10% to 12%. The R0 plants of peanut cv. Kelinci (62 R0 plants) and Singa (48 R0 plants) regenerated from PEG insensitive SE were obtained and grown in the glasshouse to produce R1 and R2 seeds.